Sosialisasi Penggunaan Media Interaktif di Sekolah Dasar - s, chelsi yuliana; Ali, Aisyah (J-Abdimas Cenderawasih, 2023)
his Community Service (PKM) activity is motivated by the challenges and needs of teachers at SDN Inpres Skouw Mabo, Jayapura City, Papua Province, in integrating technology, particularly interactive media, into the learning process. The main objectives of this activity were to enhance teachers' understanding and skills in selecting, using, and integrating various types of interactive media to create more engaging and effective learning. The implementation methods included needs assessment, material development, interactive socialization and training, and evaluation. The results showed a significant increase in teachers' understanding of the concepts and benefits of interactive media, as well as improved skills in using popular interactive platforms. Teachers' enthusiasm in designing the implementation of interactive media in their lesson plans (RPP) also increased. This activity concludes that socialization and practical training are effective in empowering teachers to adopt interactive media, which has the potential to improve the quality of learning at SDN Inpres Skouw Mabo.